The Effect of Diabetic Foot Management Education Through Audiovisual Media on the Quality of Life of Diabetes Mellitus Patients at the Internal Medicine Polyclinic of Fatmawati Hospital - Wiyono, Wiyono; Hidayatullah, Arif (IJBLE Scientific Publications Community Inc., 2025)
Diabetes Mellitus can have a long-term impact in the form of disorders in blood vessels, both macrovascular and microvascular, which can result in a decrease in quality of life encompassing physical, psychological, social, and environmental aspects. The purpose of this study is to determine the effect of Diabetes foot management education using audiovisual media on the quality of life of Diabetes Mellitus patients. This study employs a quantitative research method, specifically a pre-experimental design, utilizing the one-group pretest-posttest design (pretest-posttest in one group). Samples were obtained using a purposive sampling technique, totaling 50 patients with Diabetes Mellitus at the Internal Medicine Polyclinic of Fatmawati Hospital. The results of the study found that the average value of the respondents' quality of life before treatment was 91.44, with a variation of 6.689. The average value of the respondents' quality of life after treatment was 92.62, with a variation of 6.661. Based on the results of the paired t-test, this study showed an improvement in the quality of life of the respondents after being given education through audiovisual media, with a value of p=0.002. It is hoped that the educational video on diabetes foot management in this study can be used as an educational medium in providing nursing interventions related to efforts to improve the quality of life of Diabetes Mellitus patients.